Sunflower Cottage on Heart Lake - Robinson, Sarah (Novelist) (Robinson, Sarah (Novelist). Heart Lake., 2024)
"Amanda Riverswood has a rewarding career, a sweet cottage in her beautiful Michigan hometown of Heart Lake, and a close-knit group of fabulous friends. But after ignoring her love life for years, she's ready to step outside her comfort zone. There's only one thing that can mess up her plans for a summer of fun: her new neighbor, the very handsome, very surly Dominic Gage. Baseball star Dominic Gage was on top of the world--until a career-ending injury sent him into early retirement. Now his plan is to spend the summer sitting on his dock, reading, napping, and not talking to anyone. Especially not the cute, exasperatingly chipper girl next door. But after Dom damages Amanda's dock and offers to fix it, the two love-shy neighbors are sharing late-night conversations, laughter, and soon, a no-strings-attached fling. Could they each be what the other needs, or will their connection only lead to more heartbreak."--Back cover.